THE EFFECT OF ZEOLITE ADDITION IN RATIONS ON EGG QUALITY IN PHASE TWO OF PRODUCTION - Kurtini, Tintin (Jurnal Zeolit Indonesia, 2005)
This research was conducted to evaluate that the effect of zeolite addition in ration on egg quality in phase two of production. This experiment was arranged in a completely randomize design with 5 zeolite levels in rations (0; 2; 4; 6 and 8%) and 4 replications. The total hens were 40 of CP 909 (60 weeks of age), and this experiment was done 4 weeks. The parameters that: feed consumption, the shell thickness, fat of yolk levels, and cholesterol of yolk levels. The data were analyse by using Analysis of Variance, and orthogonal polynom test was used , analysis were in 5% significant degree. The result of this research showed that zeolite addition in ration until 8% had significant effect (P0.05) on cholesterol of yolk levels and feed consumption.